Degree of technological implementation in intravenous chemotherapy management in hospitals of the Autonomous Community of Madrid - Silvia Peña-Cabia; Belén Ortiz-Martín (Elsevier, 2017)
Objective: To understand the degree of technological implementation in the processes of preparation and administration of cytostatics drugs that is available in those hospitals of the Autonomous Community of Madrid where intravenous chemotherapy is prepared. Method: A descriptive observational study through the completion of a survey targeted to the staff responsible for the preparation of this type of treatments. Results: The degree of implementation of assisted electronic prescription is high, there is a medium degree in the case of bar code reading technology, and low in terms of vial re-labelling and gravimetric and voice control for preparation. Conclusions: There is a large room for improvement regarding traceability in the process of preparation and administration of intravenous chemotherapy